Some Inequalities of Čebyšev Type for Functions of Operators in Hilbert Spaces - Dragomir, S. S. (Sarajevo Journal of Mathematics, 2024)
Some operator inequalities for synchronous functions that are related to the Čebyšev inequality for sequences of real numbers are given. Natural examples for pairs of functions that have the same monotonicity on an interval are presented as well. 2010 Mathematics Subject Classification. 47A63, 47A99.